2008
DOI: 10.1111/j.1365-3156.2008.02057.x
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial to investigate impact of site‐based safer sex programmes in Kingston, Jamaica: trial design, methods and baseline findings

Abstract: Summaryobjective To describe the design, methods and baseline findings of a multi-level prevention intervention to increase consistent condom use among persons at public social sites in Kingston, Jamaica, who have new or concurrent sexual partnerships.methods A two-arm randomized controlled trial (RCT) of 147 sites where persons meet new sex partners. Sites were identified by community informants as places where people meet new sexual partners, which include bars, street locations, bus stops, malls and others.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…The PLACE populations in Zambia also tended to be younger and more likely to be never married. Other studies have also found the PLACE population to have more risky behaviors than the general population (Weir et al 2004; Weir et al 2008; Spiezer et al 2007). However this study is unique in being able to make district level comparisons during a specified time interval.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The PLACE populations in Zambia also tended to be younger and more likely to be never married. Other studies have also found the PLACE population to have more risky behaviors than the general population (Weir et al 2004; Weir et al 2008; Spiezer et al 2007). However this study is unique in being able to make district level comparisons during a specified time interval.…”
Section: Discussionmentioning
confidence: 94%
“…In Jamaica PLACE respondents interviewed in Montego Bay and Kingston in 2002 and 2003 were compared to respondents from the national Knowledge Attitudes Practice and Behavior Study in 2004. PLACE respondents were found to be more likely to have 2 or more partners in the past year and one or more new partner in the past year (Weir et al 2008). In a comparison of methods in Haiti, PLACE respondents interviewed in 2006/2007 had more risky sexual behavior than the population sampled by the DHS in 2005/2006 (Speizer et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The PLACE method focuses on sites where new sexual partnerships are formed because the pattern of new partnerships in a community shapes its HIV epidemic Individuals with newly acquired HIV are also more infectious which is another reason why new partnerships are so important (Anderson and May 1988, Anderson 1999). The advantages of taking prevention interventions to public places include reaching individuals who may be at risk of transmitting the infection (but who are asymptomatic) and for reaching large numbers of individuals (Weir et al 2008). …”
Section: Introductionmentioning
confidence: 99%
“…A randomized controlled trial is currently underway in Jamaica to test this methodology of targeting sites based on PLACE findings (Weir et al 2008). …”
Section: Discussionmentioning
confidence: 99%